Discussions on the talent cultivation of cyber security - Jian WENG; Chang-she MA; Liang GU (网络与信息安全学报)
Cyber security has been formally approved to be the first level discipline in June 2015.How to train the cyber security talents that meet the needs of our country has become an urgent problem to be solved in the discipline construction.Synthetical analysis of the current situation of training related talents at domestic and foreign,as well as the actual demand for the cyber security talents was presented.According to the characteristics of the talent culti-vation in cyber security,some suggestions on training the cyber security talents were given.